Applications of Information and Communication Technology in Education - Noura Saleh Albahijan; Hessa Abdullah Alsuraibi; Nouf Fahd Alzuhair (International Journal of Computers and Informatics, 2025)
This research paper is titled: Applications of Information and Communication Technology in Education. The researchers employed the analytical descriptive approach, which is the most suitable for the research topic based on gathering information, analyzing it, discussing it, and reaching conclusions and recommendations to address the issues surrounding the subject. The paper was divided into five main sections: the first section addresses the methodological framework of the research, the second focuses on the use of the internet and modern web applications, the third discusses modern technologies in the field of education and learning, the fourth covers practical applications of modern technologies in education and learning, and the fifth includes the findings, recommendations, and a list of sources and references. Among the outcomes of this paper are: enhancing the efficiency of educational staff, improving communication between educational administrations, teachers, and parents, and the emergence of distance learning systems, which have become an effective means in the educational process, contributing to the continuity of education and learning, and meeting the diverse needs of society.